Minimizing the Pain of Local Anesthesia Administration in Interventional Radiology with an Anesthetic Portal Technique - Dylan Suttle; Virpal Gill; Daniel Sheeran; Nicole Keefe; Claire Davis; James Patrie; John F. Angle (The Arab Journal of Interventional Radiology)
Objective This article assesses the effectiveness of a standardized local anesthetic (LA) technique designed to minimize the pain of local anesthesia administration in interventional radiology (IR).